Characteristics of headaches attributed to SARS-CoV-2 vaccination and factors associated with its frequency and prolongation: a cross-sectional cohort study - Jameie, Melika; Togha, Mansoureh; Azizmohammad Looha, Mehdi; Jafari, Elham; Yazdan Panah, Mohammad; Hemmati, Nima; Nasergivehchi, Somayeh (Frontiers in Neurology, 2023)
Background Headache is the most frequent neurological adverse event following SARS-CoV-2 vaccines. We investigated the frequency, characteristics, and factors associated with post-vaccination headaches, including their occurrence and prolongation (≥ 48 h). Methods In this observational cross-sectional cohort study, retrospective data collected between April 2021–March 2022 were analyzed. Univariate and multivariate logistic regressions were used to evaluate the effect of clinicodemographic factors on the odds of post-vaccination headache occurrence and prolongation. Results Of 2,500 people who were randomly sent the questionnaire, 1822 (mean age: 34.49 ± 11.09, female: 71.5%) were included. Headache prevalence following the first (V1), second (V2), and third (V3) dose was 36.5, 23.3, and 21.7%, respectively (p < 0.001). Post-vaccination headaches were mainly tension-type (46.5%), followed by migraine-like (36.1%). Headaches were mainly bilateral (69.7%), pressing (54.3%), moderate (51.0%), and analgesic-responsive (63.0%). They mainly initiated 10 h [4.0, 24.0] after vaccination and lasted 24 h [4.0, 48.0]. After adjusting for age and sex, primary headaches (V1: aOR: 1.32 [95%CI: 1.08, 1.62], V2: 1.64 [1.15, 2.35]), post-COVID-19 headaches (V2: 2.02 [1.26, 3.31], V3: 2.83 [1.17, 7.47]), headaches following the previous dose (V1 for V2: 30.52 [19.29, 50.15], V1 for V3: 3.78 [1.80, 7.96], V2 for V3: 12.41 [4.73, 35.88]), vector vaccines (V1: 3.88 [3.07, 4.92], V2: 2.44 [1.70, 3.52], V3: 4.34 [1.78, 12.29]), and post-vaccination fever (V1: 4.72 [3.79, 5.90], V2: 6.85 [4.68, 10.10], V3: 9.74 [4.56, 22.10]) increased the odds of post-vaccination headaches. Furthermore, while primary headaches (V1: 0.63 [0.44, 0.90]) and post-COVID-19 headaches (V1: 0.01 [0.00, 0.05]) reduced the odds of prolonged post-vaccination headaches, psychiatric disorders (V1: 2.58 [1.05, 6.45]), headaches lasting ≥48 h following the previous dose (V1 for V2: 3.10 [1.08, 10.31]), and migraine-like headaches at the same dose (V3: 5.39 [1.15, 32.47]) increased this odds. Conclusion Patients with primary headaches, post-COVID-19 headaches, or headaches following the previous dose, as well as vector-vaccine receivers and those with post-vaccination fever, were at increased risk of post-SARS-CoV-2-vaccination headaches. Primary headaches and post-COVID-19 headaches reduced the odds of prolonged post-vaccination headaches. However, longer-lasting headaches following the previous dose, migraine-like headaches at the same dose, and psychiatric disorders increased this odd.